2014
DOI: 10.1111/jsm.12450
|View full text |Cite
|
Sign up to set email alerts
|

Clitoral Size and Location in Relation to Sexual Function Using Pelvic MRI

Abstract: Introduction The female sexual response is dynamic; anatomic mechanisms may ease or enhance the intensity of orgasm. Aim The aim of this study is to evaluate the clitoral size and location with regard to female sexual function. Methods This cross-sectional TriHealth Institutional Board Review approved study compared 10 sexually active women with anorgasmia to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 28 publications
0
23
1
2
Order By: Relevance
“…Nevertheless, Huffman et al concluded an increase in clitoral size in normal female subjects, from childhood to the fourth decade of life to the postmenopausal years [12]. Several studies [13,14] also support clitoral tissue being responsive to serum hormones. A recent study [14] in women matched by age and body mass index revealed that women with self-reported anorgasmia had a significantly smaller clitoral glans and greater distance from the clitoral complex to the vaginal lumen on pelvic MRI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, Huffman et al concluded an increase in clitoral size in normal female subjects, from childhood to the fourth decade of life to the postmenopausal years [12]. Several studies [13,14] also support clitoral tissue being responsive to serum hormones. A recent study [14] in women matched by age and body mass index revealed that women with self-reported anorgasmia had a significantly smaller clitoral glans and greater distance from the clitoral complex to the vaginal lumen on pelvic MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies [13,14] also support clitoral tissue being responsive to serum hormones. A recent study [14] in women matched by age and body mass index revealed that women with self-reported anorgasmia had a significantly smaller clitoral glans and greater distance from the clitoral complex to the vaginal lumen on pelvic MRI. Such findings support clitoral characteristics having an impact on female sexual symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Sonography has also shown that the clitoral roots undergo movement and pressure when the vagina is penetrated and perineal contractions ensue [10]. Furthermore, MRI studies have demonstrated larger clitoral glans size and shorter distance from the clitoris to the vaginal lumen in women endorsing normal orgasmic function [59]. Likewise, as previously mentioned, women with shorter clitoral-urethral distances were better able to achieve VAO [29].…”
Section: The Clitoris and Vaginal Eroticismmentioning
confidence: 81%
“…Women 18 to 55 years old were eligible if sexually active (defined as at least four sexual encounters in the month before enrollment), were in a monogamous relationship, and had a documented diagnosis of HSDD as the primary cause of FSD (defined as a non-adjusted score ≤ 6 in the desire domain [range = 0–10] of the Female Sexual Function Index [FSFI] questionnaire) 12 . Exclusion criteria included postmenopausal women (defined as absence of menstruation in the prior 12 months), pelvic pain or dyspareunia as the primary cause of FSD (defined as a non-adjusted score ≤ 6 in the pain domain [range = 0–10] of the FSFI), prior hysterectomy and/or oophorectomy, history of chemotherapy and/or pelvic irradiation, use of hormonal contraception or hormone replacement therapy, active skin infection or disease preventing insertion of acupuncture needles, known allergy to acupuncture needles, or blood dyscrasia.…”
Section: Methodsmentioning
confidence: 99%